PROTECTION OF CHILDREN AND DEVELOPMENT OF THE CRIMINAL LEGISLATION - Serikbayev Талгар Абдунабиевич (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2023)
In this scientific article the author considers a criminal – legal protection of child`s in Republik Kazakhstan.